A Novel Sesterterpenoid, Petrosaspongin and γ-Lactone Sesterterpenoids with Leishmanicidal Activity from Okinawan Marine Invertebrates - Takahiro Jomori; Nanami Higa; Shogo Hokama; Trianda Ayuning Tyas; Natsuki Matsuura; Yudai Ueda; Ryo Kimura; Sei Arizono; Nicole Joy de Voogd; Yasuhiro Hayashi; Mina Yasumoto-Hirose; Junichi Tanaka; et al. (Marine Drugs)
Leishmaniasis is a major public health problem, especially affecting vulnerable populations in tropical and subtropical regions. The disease is endemic in 90 countries, and with millions of people at risk, it is seen as one of the ten most neglected tropical diseases. Current treatments face challenges such as high toxicity, side effects, cost, and growing drug resistance. There is an urgent need for safer, affordable treatments, especially for cutaneous leishmaniasis (CL), the most common form. Marine invertebrates have long been resources for discovering bioactive compounds such as sesterterpenoids. Using bioassay-guided fractionations against cutaneous-type leishmaniasis promastigotes, we identified a novel furanosesterterpenoid, petrosaspongin from Okinawan marine sponges and a nudibranch, along with eight known sesterterpenoids, hippospongins and manoalides. The elucidated structure of petrosaspongin features a β-substituted furane ring, a tetronic acid, and a conjugated triene. The sesterterpenoids with a γ-butenolide group exhibited leishmanicidal activity against Leishmania major promastigotes, with IC50 values ranging from 0.69 to 53 μM. The structure–activity relationship and molecular docking simulation suggest that γ-lactone is a key functional group for leishmanicidal activity. These findings contribute to the ongoing search for more effective treatments against CL.